Effects of electron beam irradiation on microbial contamination and quality of Astragali Radix - Fu, Meng; Wang, Dan; Wang, Gang; Huang, Ming; Tang, Yiweng (Food Science and Technology, 2023)
In this study, astragali radix (AR) was irradiated at doses of 3, 5, 7, 10 and 18 kGy of electron-beam, to investigate the effects on the microbial content, physicochemical quality, and antioxidant activity. Results showed that AR was decontaminated at 7 kGy irradiation, but its color was altered. The total flavonoid, total phenol content, DPPH and ABTS radical scavenging ability increased with an increase in radiation dose for AR. In conclusion, electron beam irradiation can effectively kill the surface microorganisms of AR, increase the contents of flavonoids and total phenols, and increase its free radical scavenging activity without affecting its main active components.